Communicative (inter-)action transcending the police investigative interview room - Hohl Zürcher, Franziska; Capus, Nadja (Language and Law / Linguagem e Direito, 2023)
Police officers anticipate the evidential function and the absent audience while interviewing and recording investigative interviews. This audience consists of judges charged with taking procedural decisions based, among other things, on their reception of these written records. Qualitative studies have revealed that interviewers use confrontational questions to communicate their doubt regarding the interviewee’s credibility to the audience, and that they formulate the questions in the written record more confrontationally than in the actual interview for the same reason. However, so far, insufficient knowledge exists about the intended effect: Is the audience receptive to the police officer’s doubt when reading the written record? Our paper reports an experiment testing the effects of this confrontational questioning style. The results show that there is, indeed, a communicative (inter-)action transcending the police investigative interview room: the audience is receptive to the police officer’s doubt transmitted via the questioning style reported in the written record.